Primary Aluminium Production and Energy Intensity: Long-Run Dynamics Explored through the ARDL Approach - Safarov, Jamil I.; Hasanov, Ramil I.; Safarli, Arzu (International Journal of Energy Economics and Policy, 2025)
The escalating global demand for aluminum has highlighted various environmental challenges associated with its production, with energy consumption emerging as the predominant factor. Aluminum production is inherently energy-intensive, necessitating a thorough understanding of the relationship between energy consumption and production efficiency to enhance sustainability across both economic and environmental dimensions. It is particularly crucial as the industry faces increasing pressure to minimize its environmental impact while simultaneously meeting growing global demand. This study examines the long-term dynamics between global primary aluminum production and energy intensity from 1980 to 2023 using the Autoregressive Distributed Lag (ARDL) approach. This econometric method facilitates a detailed examination of the temporal interactions between these two pivotal variables. The analysis reveals a significant inverse relationship, where a 1-unit reduction in smelting energy intensity correlates with an approximate 10.76-unit increase in primary aluminum production. This finding underscores the critical importance of improving energy efficiency within the aluminum sector as a strategy to foster higher production while concurrently reducing energy consumption. Additionally, the study highlights the significance of technological advancements and process optimization in mitigating energy intensity, reinforcing their role in fostering sustainable production practices.